2020
DOI: 10.1186/s12933-020-01032-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of sleep disturbance with risk of cardiovascular disease and all-cause mortality in patients with new-onset type 2 diabetes: data from the Korean NHIS-HEALS

Abstract: Background: Sleep disturbance has been significantly associated with the incidence of cardiovascular disease (CVD) in the general population. However, despite the common prevalence of sleep disturbance in patients with type 2 diabetes, its relationship with the risk of CVD remains unclear. Here, we have examined the association of sleep disturbance with the incidence of all CVD and all-cause mortality in patients with newly-diagnosed type 2 diabetes. Methods: We used the Korean National Health Insurance Servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Nature exposure during lockdown has been associated with reduced sleep disturbance (Table 2). Inadequate sleep and sleep disturbances are considered common risk factors for several mental and physical illnesses such as obesity, cancer and cardiovascular diseases (Shin et al, 2020;Choi and Choi, 2020;Muscogiuri et a., 2019;Shankar et al, 2010). Spano et al (2021) and Corley et al (2021) indicated that nature exposure, such as viewing nature through windows and gardening during the lockdowns, was negatively associated with sleep disturbance.…”
Section: Sleepmentioning
confidence: 99%
“…Nature exposure during lockdown has been associated with reduced sleep disturbance (Table 2). Inadequate sleep and sleep disturbances are considered common risk factors for several mental and physical illnesses such as obesity, cancer and cardiovascular diseases (Shin et al, 2020;Choi and Choi, 2020;Muscogiuri et a., 2019;Shankar et al, 2010). Spano et al (2021) and Corley et al (2021) indicated that nature exposure, such as viewing nature through windows and gardening during the lockdowns, was negatively associated with sleep disturbance.…”
Section: Sleepmentioning
confidence: 99%
“…In a large cohort of adults from the USA, risk of mortality in type 2 diabetes mellitus patients (compared to non-diabetics) increased from 1.84 with a sleep duration of 7 h to 2.78 and 3.67 for 5 and 10 h respectively [13]. Similarly, data from the Korean National health insurance program found that newly diagnosed type 2 diabetes mellitus patients with sleep disturbances have a higher incidence of cardiovascular disease and all-cause mortality [14]. Poor sleep quality has also been shown to be associated with microvascular complications such as diabetic retinopathy [15].…”
mentioning
confidence: 94%
“…It is important for persons with type 2 diabetes (T2D) because they are susceptible to developing micro- and macro-vascular diseases [ 17 ], and sleep disorders affect blood sugar and insulin levels [ 18 , 19 ]. A recent study reported sleep disturbance is significantly associated with an increased risk of CVD and all-cause mortality in patients with new-onset T2D [ 20 ], and a long sleep duration (≥ 9 h/day) has been shown to be associated with an increased all-cause mortality in persons with T2D [ 21 ]. A higher level of HbA1c can be found in patients with diabetes with short and long sleep durations than in those with medium sleep duration [ 22 ].…”
Section: Introductionmentioning
confidence: 99%